Optimized design of 3-DOF buoy wave energy converters under a specified wave energy spectrum. (November 2021) - Tao, Ji; Cao, Feifei; Dong, Xiaochen; Li, Demin; Shi, Hongda
Abstract: The oscillating body is one of the most common wave energy converters (WECs) owing to its simple structure and adaptability to various wave directions. In recent years, many researchers have focused on a multi-freedom oscillating body because of its high energy capture efficiency. The choice of geometrical settings for this WEC is of great importance for increasing energy capture. In this study, the effects of radius, draft, and vertical mass distribution on the hydrodynamic performance and output power were investigated. A methodology for the optimum design of 3-degree of freedom (DOF) buoy WEC for a specified wave energy spectrum based on hydrodynamics analysis and statistical methods is presented. The optimization object is based on a cylindrical buoy that considers a linear power take-off (PTO) system. A numerical model was established to determine the effects of geometrical parameters using a boundary element method (BEM) solver and was validated by the experimental data. This study also applied this optimization method to a case study in a certain sea area in northern China. The results obtained using this method significantly improve the computational efficiency. Thus, this paper provides a guidance for the design of the optimization of the prototype buoy under certain wave conditions.